Renewable energy in power systems - Infield, David; Freris, Leon (Wiley, 2020)
"With the growth in renewable energy (RE) generation installed capacity, many countries such as the UK are relying on higher levels of RE generation to meet targets for reduced greenhouse gas emissions. In the face of this, the integration issue is now of increasing concern, in particular to system operators. This updated text describes the individual renewable technologies and their power generation characteristics alongside an expanded introduction to power systems and the challenges posed by high levels of penetrations from such technologies. Features of this edition: Covers power conditioning, the characteristics of RE generators, with emphasis on their time varying nature, and the use of power electronics in interfacing RE sources to grids. Outlines up to date RE integration issues such as power flow in networks supplied from a combination of conventional and renewable energy sources. Update on the economics of power generation and the role of markets in delivering investment in sustainable solutions by specialist contributors. nsiders the challenge of maintaining power balance in a system with increasing RE input, including recent moves toward power system frequency support from RE sources. Offers an insightful perspective on the shape of future power systems including offshore networks and demand side management. Worked examples enhance this edition's suitability as a textbook for introductory courses in RE systems technology. Firmly established as an essential reference, Renewable Energy in Power Systems, Second Edition will prove a real asset to engineers and others involved in both the growing power and renewables sector. This text should also be of particular benefit to students of electrical power engineering and will appeal to non-specialists through the inclusion of background material covering the basics of electricity generation"--